A preliminary survey of arthropod diversity through pitfall trap in the selective habitats at Rajshahi University Campus (University Journal of Zoology, Rajshahi University, 2012)
DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9471UJZRU 2010; 29(1): 73-75Key words: arthropod; diversity; insects; pitfall trap,